Vietnam development report 2010 Modern institutions - The World Bank (Hà Nội World Bank, 2009)
This Vietnam development report focuses on devolution and accountability, two aspects of modern institutions that are the essense of Vietnam's experience in the past two decades
Keywords: Chủ nghĩa cộng sản -- Việt Nam; Phân cấp trao quyền; Trách nhiệm giải trình